Effect of two post‐surgical cleansing protocols on early periodontal wound healing and cytokine levels following osseous resective surgery: A randomized controlled study. Issue 4 (10th April 2019) - Sijari, Ziad; Romano, Federica; Ciardo, Gabriele; Martella, Vanessa; Maggiora, Marina; Bottone, Mario; Aimetti, Mario
Abstract: Objectives: The aim of this RCT study was to compare early wound healing and gingival crevicular fluid cytokine levels of patients treated with two different post‐surgical cleansing protocols. Methods: A total of 30 chronic periodontitis patients scheduled for osseous resective surgery with fibre retention technique were randomly assigned to follow one of two post‐surgical protocols. Patients assigned to the test protocol (n = 15) were instructed to brush the surgical area with a sonic toothbrush starting the day after surgery in addition to 0.12% chlorhexidine (CHX) rinsing, while patients following the control protocol (n = 15) rinsed only with 0.12% CHX solution and resumed mechanical cleansing with a manual toothbrush on day 14 after surgery. Interleukin (IL)‐1β and IL‐8 levels were assessed before and 14 days post‐operatively in gingival crevicular fluid. Patients were recalled on day 7, 14, 21 and 28 after surgery for clinical assessment. Pain was self‐reported by a visual analogue scale. Results: Lower early wound healing scores, higher bacterial plaque reduction and milder inflammatory response were observed at the surgical sites in the test group on day 7, 14 and 28 when compared to the control group ( P  < 0.01). The faster wound healing process was modulated by a statistically significant decrease in IL‐1β and IL‐8 levels on day 14 in the sonic group. The intensity of pain was similar between groups. Conclusions: The introduction of sonic toothbrush on the first post‐operative day as an adjunct of daily CHX rinsing would seem to accelerate early wound healing.